Ideals and free Pairs in the semigroup β ℤ - Protasov, I. V. (Ukrains’kyi Matematychnyi Zhurnal, 1997)
We prove that the equations ξ+x=mξ+y, x+ξ=y+mξ have no solutions in the semigroup β ℤ for every free ultrafilter ξ and every integer m∈0, 1. We study semigroups generated by the ultrafilters ξ, mξ. For left maximal idempotents, we prove a reduced hypothesis about elements of finite order in β ℤ.